Anthocyanins in the Management of Metabolic Syndrome: A Pharmacological and Biopharmaceutical Review - Naseri, Rozita; Farzaei, Fatemeh; Haratipour, Pouya; Nabavi, Seyed Fazel; Habtemariam, Solomon; Farzaei, Mohammad Hosein; Khodarahmi, Reza; Tewari, Devesh; Momtaz, Saeideh (Frontiers in Pharmacology, 2018)
The term “metabolic syndrome” (MetS) refers to a combination of diabetes, high blood pressure, and obesity. The origin of MetS includes a combination of multiple factors, such as sedentary lifestyle, unhealthy diet choice, and genetic factors. MetS is highly prevalent and adversely affects the general population by elevating risk of cardiovascular complications, organ failure, and much other pathology associated with late-stage diabetes. Anthocyanins (ANTs) are health-promoting bioactive compounds belonging to the flavonoids subclass of polyphenols. Numerous studies have reported the potential therapeutic benefits on MetS syndrome and diabetes from fruits rich in ANTs. This review summarizes the role of several dietary ANTs on preventing and managing MetS as well as the pharmacological mechanisms and biopharmaceutical features of their action. We also discuss potential nanoformulation and encapsulation approaches that may enhance the bioefficacy of ANTs in MetS. Experiments have demonstrated that ANTs may attenuate the symptoms of MetS via improving insulin resistance, impaired glucose tolerance, dyslipidaemia, cholesterol levels, hypertension, blood glucose, protecting β cells, and preventing free radical production. In brief, the intake of ANT-rich supplements should be considered due to their plausible ability for prevention and management of MetS. Additionally, randomized double-blind clinical trials are obligatory for evaluating the bioefficacy and pharmacological mechanisms of ANTs and their pharmaceutical formulations in patients with MetS.